Adaptive Bifunctional Electrocatalyst of Amorphous CoFe Oxide @ 2D Black Phosphorus for Overall Water Splitting - Li, Xingyun; Xiao, Liangping; Zhou, Ling; Xu, Qingchi; Weng, Jian; Xu, Jun; Liu, Bin (Angewandte Chemie International Edition, 2020)
Water electrolysis offers a promising green technology to tackle the global energy and environmental crisis, but its efficiency is greatly limited by the sluggish reaction kinetics of both the cathodic hydrogen evolution reaction (HER) and anodic oxygen evolution reaction (OER). In this work, by growing amorphous multi‐transition‐metal (cobalt and iron) oxide on two‐dimensional (2D) black phosphorus (BP), we develop a bifunctional electrocatalyst (CoFeO@BP), which is able to efficiently catalyze both HER and OER. The overpotentials for the hybrid CoFeO@BP catalyst to reach a current density of 10 mA cm−2 in 1 m KOH are 88 and 266 mV for HER and OER, respectively. Based on a series of ex‐situ and in situ investigations, the excellent catalytic performance of CoFeO@BP is found to result from the adaptive surface structure under reduction and oxidation potentials. CoFeO@BP can be transformed to CoFe phosphide under reduction potential, in situ generating the real active catalyst for HER. By growing amorphous multi‐transition‐metal (cobalt and iron) oxide on two‐dimensional (2D) black phosphorus (BP), a bifunctional electrocatalyst (CoFeO@BP), which is able to efficiently catalyze both HER and OER was developed. The overpotentials for the hybrid CoFeO@BP catalyst to reach a current density of 10 mA cm−2 in 1 m KOH are 88 and 266 mV for HER and OER, respectively.